Ocean warming is projected to speed development and decrease survival of crab larvae - Marochi, Murilo Zanetti [UNESP]; Costa, Tânia Marcia [UNESP]; Buckley, Lauren B. (Elsevier, 2021)
Increasing mean ocean temperatures, due to climate change, are recognized as one of the biggest threats to marine ecosystems and the goods and services they provide. The vulnerability of an organism to climate change can be projected as a function of sensitivity and exposure during growth. These projections have becoming increasingly necessary to improve ecosystem and resource management. We estimate how ocean warming will impact crab populations of commercial interest on the tropical and subtropical Atlantic coast. A compile of laboratory data was used to estimate the temperature dependence of survival and development for Ucides cordatus and Menippe nodifrons. A decrease in mean survival probability and mean development time, under ocean warming scenarios through 2100 are projected. Lower survival probabilities and development time were projected for lower latitudes compared to higher latitudes. Increasing temperatures along the Atlantic coast will likely impact larval settlement with consequences for population maintenance and connectivity among populations. As indirect consequences, ecological and economic disturbances are expected.
Keywords: Climate change; Larval development; Larval settlement; Larval survival; Thermal physiology; Thermal stress